2011
DOI: 10.4061/2011/591793
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Incidence of Fractures in Solid-Organ Transplant Recipients on Glucocorticoid-Sparing Immunosuppressive Regimens

Abstract: This study was conducted to assess the occurrence of fractures in solid-organ transplant recipients. Methods. Medical record review and surveys were performed. Patients received less than 6 months of glucocorticoids. Results. Of 351 transplant patients, 175 patients provided fracture information, with 48 (27.4%) having fractured since transplant (2–6 years). Transplants included 19 kidney/liver (50% male), 47 kidney/pancreas (53% male), 92 liver (65% male), and 17 pancreas transplants (41% male). Age at transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The secondary analyses conducted to date raise concerns about the preconception that ECSW regimens would substantially lower fracture risk. [15][16][17][18] Trials by Woodle et al 17 and Rizzari et al 16 found no difference in fracture rates. However, fractures were a secondary outcome, and spine fractures, among the most common types of post-transplant fractures, 4 were not ascertained.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The secondary analyses conducted to date raise concerns about the preconception that ECSW regimens would substantially lower fracture risk. [15][16][17][18] Trials by Woodle et al 17 and Rizzari et al 16 found no difference in fracture rates. However, fractures were a secondary outcome, and spine fractures, among the most common types of post-transplant fractures, 4 were not ascertained.…”
Section: Discussionmentioning
confidence: 96%
“…However, fractures were a secondary outcome, and spine fractures, among the most common types of post-transplant fractures, 4 were not ascertained. A retrospective study by Edwards et al 18 found that corticosteroid withdrawal did not result in a fracture reduction benefit. However, the corticosteroid withdrawal regimens in the study were not reflective of current ECSW protocols, and the patient population was not reflective of most patients managed with ECSW: patients were managed with up to 6 months of corticosteroids, had type 1 diabetes, and received simultaneous kidneypancreas transplantation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a small study of kidney transplant recipients detected no difference in bone loss between those who received CsA monotherapy and those who received azathioprine plus prednisolone [45] and a prospective study found that cumulative CsA dose was associated with bone loss in the 2 years following transplant, independent of the effect of steroids [46]. In a study of patients on GC-sparing regimens, less than 6 months of GCs after transplant, 27% sustained a fracture, similar to rates in patients on conventional GC-containing regimens [47].…”
Section: Cyclosporinesmentioning
confidence: 64%
“…In a large observational study of 77 430 RTRs who were followed for a median of 3.9 years, glucocorticoid withdrawal was associated with a 31 % reduction in fracture risk, and the incidence of fractures was higher in those patients taking glucocorticoids when discharged . In a smaller study of 175 solid organ transplants recipients, those with limited glucocorticoid exposure had similar fracture rates to those on conventional immunosuppressive protocols . Glucocorticoid withdrawal in RTRs has also been associated with improved BMD parameters 1‐year post‐transplantation .…”
Section: Introductionmentioning
confidence: 99%